Case report: Fatal outcome of pyridoxine-dependent epilepsy presenting as respiratory distress followed by a circulatory collapse - Aquilano, Giulia; Linnér, Agnes; Ygberg, Sofia; Stödberg, Tommy; Henckel, Ewa (Frontiers in Pediatrics, 2022)
Pyridoxine-dependent epilepsy is a rare autosomal recessive disease usually associated with neonatal seizures that do not respond to common antiseizure medications but are controlled by pyridoxine administration. Because the symptoms can mimic common neonatal disorders, the diagnosis can be initially missed or delayed. We report a fatal case of a boy who was initially diagnosed with respiratory distress, birth asphyxia and persistent pulmonary hypertension and whose condition rapidly deteriorated during the first day of life.